English learning style preferences: A case study of civil engineering students - Sylvia Irene Persulessy; Yelliza Yelliza; Ahmad Nusi; Juvrianto Chrissunday Jakob; Hindri Febri Ana Sari (Universitas Islam Malang, 2023)
In learning English, it is clearly seen that students have their own ways and abilities to understand information or learning materials. The method used by students in understanding the information is generally known as learning style. This study aims to identify the dominant learning style used by students in learning English at civil engineering class. This study was survey research. There are two types of learning styles studied. First, it can be seen from the perceptual aspect which has 3 types of learning styles, namely visual, auditory, and kinesthetic. Second, learning styles are seen from the social aspect which consists of 2 types, namely groups and individuals. The participants in this study were 248 students briefly divided into 9 classes. In determining the participants, the researcher precisely used a total sampling technique. Furthermore, the researcher used a questionnaire as an instrument to obtain data. The results of the study strongly showed that students used all learning styles, namely visual, auditory, kinesthetic, group, and individual. Based on the data obtained and analyzed, the highest percentage of learning styles for the perceptual aspect is visual with a total percentage of 45.5%. Then, for the social aspect, which gained a percentage of 44.3%. Based on the data obtained in this study, it can be concluded that the learning style of civil engineering students is more dominant using the perceptual learning style compared to the social learning style, and this can be seen from the data presented in this study.